Interactive exhibition on climate geoengeneering: empowering future teachers for sociopolitical action - Linhares, Elisabete (2019)
The present case study, involving 19 pre-service teachers, intends to identify the potentialities and the limitations associated with the development of interactive exhibitions on socio-scientific issues as a strategy to empower future teachers for sociopolitical action. An interactive scientific exhibition developed accordingly to the IRRESISTIBLE project module "Geoengineering: Climate Control?" sought to create opportunities for students to work collaboratively, to take responsibility and to participate in activism initiatives. The results suggest positive impacts on students’ scientific knowledge, exhibitions’ development skills and empowerment for action. The main difficulties are focused on group work and time management. This pedagogical initiative allowed the development of competences considered important for citizens’ scientific literacy and active involvement in sociopolitical action.